2015
DOI: 10.1192/bjp.bp.114.155820
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antidepressant therapy and mortality rates in ischaemic heart disease: cohort study

Abstract: Adherence to antidepressant pharmacotherapy is associated with reduced all-cause mortality in a population-based large sample cohort of patients with IHD. Physicians and health policy decision-makers should step up their efforts to sustain and enhance these patients' adherence to their antidepressant regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…Similarly to our previous reports on mortality in other AD‐using populations (Krivoy et al, ; Krivoy et al, ; Krivoy et al, ; Shoval et al, ), our unadjusted analyses in the present study showed an increased rate of death in the higher adherence levels. As previously discussed broadly in these publications, we attribute this finding mainly to a more drug adherent behavior in the older and highly comorbid patients, therefore such findings demonstrate the importance of having the capability to adjust for important confounders.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly to our previous reports on mortality in other AD‐using populations (Krivoy et al, ; Krivoy et al, ; Krivoy et al, ; Shoval et al, ), our unadjusted analyses in the present study showed an increased rate of death in the higher adherence levels. As previously discussed broadly in these publications, we attribute this finding mainly to a more drug adherent behavior in the older and highly comorbid patients, therefore such findings demonstrate the importance of having the capability to adjust for important confounders.…”
Section: Discussionsupporting
confidence: 92%
“…This relationship is systematically repeated in all subtypes of cancer we studied, except for melanoma. Similarly to our previous studies in the general population and in certain other major physical disorders (Krivoy et al, ; Krivoy et al, ; Krivoy et al, ; Shoval et al, ), the beneficial effect of adherence to AD may be at least equally important in the high‐risk population of patients with cancer. Psychiatrists, Oncologists, and primary‐care physicians should step up their efforts to sustain and enhance their patients' adherence to AD, as it may be associated with increased life expectancy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our measure of adherence was shown to be reliable (Krivoy et al 2015;Singer et al 2012). The large sample size (N =310,994) encompassed a nationwide sample of all patients who used AD along 4 years in the CHS database without an age limitation.…”
Section: Discussionmentioning
confidence: 93%
“…Some evidence suggests increased medical risk: antidepressants combined with phenothiazines increase risk of sudden cardiac death shortly after myocardial infarction more than phenothiazines alone [67], and a long-term, non-randomized observational study found increased mortality over up to 42 months follow-up for patients taking serotonin reuptake inhibitors after myocardial infarction [68]. However, improved adherence (i.e., more exposure) to antidepressants was associated with reduced mortality in a 4-year follow-up study in ischemic heart disease patients with depression [69]. A 2011 metaanalysis [70] concluded that SSRIs improve depression but do not have a significant effect on readmission for CHD or all-cause mortality, although point-estimates of effect were in the direction of benefit.…”
Section: Effects Of Antidepressants On the Course Of Cardiovascular Dmentioning
confidence: 94%